Effectiveness of Anti-Corruption Education in Changing Human Character - Aminullah, Aminullah; sukarman, sukarman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Corruption is an extraordinary crime, the impact of criminal acts of corruption can damage democratic values, morality, harm state finances, violate the social and economic rights of the community and constitute a threat to the ideals of a just and prosperous society, in In Indonesia there are three law enforcement agencies that have the authority to handle corruption cases, namely the Police, Prosecutor's Office and Corruption Eradication Commission. The government responded to handling corruption with educational media by issuing Permenristekdikti policy no. 33 of 2019 concerning the Obligation to Implement Anti-Corruption Education (PAK) in Higher Education. Corruption from a legal perspective is considered an extraordinary crime because it can have extraordinary impacts. Furthermore, the phenomenon of corruption crimes from a sociological perspective is considered a social disease that can occur in all sectors and is carried out by all levels of society. From this explanation, anti-corruption becomes an antithesis. The definition of anti-corruption is all actions, words or deeds that oppose corruption and all its forms. Someone who understands the meaning of anti-corruption will act in accordance with the values of integrity. The nine integrity values are honest, independent, responsible, brave, simple, caring, disciplined, fair and hardworking, or what is abbreviated as